The complete chloroplast genome of Clematis hexapetala (Ranunculaceae) and its phylogenetic analysis. Issue 6 (3rd June 2022) - Cui, Yi; Sun, Yingxin; Ding, Yanzhe; Liu, Jing; Han, Zhongming; Wang, Yunhe; Han, Mei; Yang, Limin
Abstract: Clematis hexapetala Pall. (1776) is a traditional Chinese medicine belonging to the Ranunculaceae. In this study, the complete chloroplast genome was sequenced through Illumina platform, cp was circular DNA molecule of 159, 538 bp in length with a typical quadripartite structure, consisting of four regions: two copies of inverted repeat region (IRs: 31, 039 bp), a large single-copy (LSC: 79, 333 bp) region, a small single-copy (SSC: 18, 127 bp) region. The chloroplast genome encodes a total of 135 genes, including 91 CDS genes, 36 tRNA genes, 8 rRNA genes. Phylogenetic analysis based on complete genes shows that C. hexapetala closely related to  C. taeguensis  in the genus  Clematis . This study improves our comprehension of the chloroplast genome and its phylogenetic relationships within Ranunculaceae.